Carboxylated carbon quantum dot-induced binary metal–organic framework nanosheet synthesis to boost the electrocatalytic performance. (April 2022) - Song, Daqi; Guo, Huazhang; Huang, Kai; Zhang, Huiyi; Chen, Jia; Wang, Liang; Lian, Cheng; Wang, Yong
Graphical abstract: Abstract: Two-dimensional (2D) metal–organic framework nanosheets (MOF NSs) are robust candidates for highly efficient oxygen evolution reactions (OERs). However, challenging top-down synthesis strategies still hinder electrocatalytic applications. Here, we directly fabricate 2D NiFe-MOF NSs induced by carboxylated carbon quantum dots (CQDs-COOH) in-situ through a one-step room-temperature "bottom-up" synthesis strategy without additional complex and low-yield exfoliation processes. Density functional theory calculations confirm that CQDs-COOH enlarges the layer spacing of the NiFe-MOF and effectively induces the formation of NiFe-MOF NSs via electron-withdrawing –COOH groups. Furthermore, CQDs-COOH increases the positive charge on the active sites and improves the OER performance of NiFe-MOF. NiFe-MOF NSs@CQDs-COOH shows a low overpotential of 261 mV to reach a 10-mA cm −2 current density and a small Tafel slope of 56 mV dec −1 and exhibits high durability after 48 h of long-term testing. These excellent electrocatalytic performances are also illustrated by application in a rechargeable Zn-air flow battery, which demonstrates an open-circuit voltage of 1.42 V, a 133.5° static contact angle, and an excellent specific capacity of 895.5 mAh g Z n - 1 . The universal CQD-induced approach for bottom-up synthesis of high-efficiency 2D MOF NSs will facilitate the progress of 2D catalysts to construct state-of-the-art energy conversion and storage devices.